Saxagliptin Efficacy and Safety in Patients With Type 2 Diabetes and Moderate Renal Impairment. Issue 3 (September 2016) - Perl, Shira; Cook, William; Wei, Cheryl; Iqbal, Nayyar; Hirshberg, Boaz
Abstract Introduction Type 2 diabetes (T2D) is the leading cause of chronic kidney disease (CKD). The recommended dose of the dipeptidyl peptidase-4 inhibitor saxagliptin is 2.5 mg in patients with moderate or severe renal impairment (creatinine clearance ≤50 mL/min). In this post hoc analysis, we assessed the effect of saxagliptin 2.5 and 5 mg/day versus placebo on glycemic measures in patients with T2D and estimated glomerular filtration rate 45–60 mL/min/1.73 m2 . Methods Efficacy and safety data were pooled from nine 24-week, randomized, placebo-controlled clinical trials. Results The majority (56–61%) of patients were women aged <65 years with glycated hemoglobin (A1C) 8.1–8.2%; half of the patients had a T2D duration ≥5 years. Mean change from baseline in A1C was significantly greater with saxagliptin 2.5 (–0.6%, P  = 0.036 vs placebo) and 5 mg/day (–0.9%, P  < 0.001 vs placebo) compared with placebo (–0.2%). There were numerically greater reductions in fasting plasma glucose and 2-h postprandial glucose, and a significantly greater proportion of patients achieved A1C <7% with saxagliptin 5 mg/day (44.8%) compared with placebo (20.0%, P  = 0.004 vs placebo). The incidence of hypoglycemia was not significantly different across groups (16.2% in the saxagliptin 5-mg/day, 12.2% in the saxagliptin 2.5-mg/day, and 11.3% in the placebo groups). Conclusion These results suggest that saxagliptin 2.5 and 5 mg/day improve glycemic control and are generally well tolerated in patients with T2D and moderate CKD. Trial registration ClinicalTrials.gov identifier, NCT00121641, NCT00316082, NCT00698932, NCT00918879, NCT00121667, NCT00661362, NCT00313313, NCT00295633, NCT00757588. Funding AstraZeneca, Gaithersburg, MD, USA.